Evaluation of the Oca Chatbot System as a Customer Complaint Service of PT Telkom Witel West Sumatra - angelina, Tamara; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the evaluation of the Online Customer Assistant (OCA) chatbot as a customer complaint service at PT Telkom Indonesia, particularly for IndiHome users at Plasa Witel Sumbar, Padang. The implementation of this digital service was intended to enhance accessibility, reduce customer queues, and streamline complaint handling. However, several challenges remain, including the chatbot’s limited ability to resolve complex technical issues, reliance on standardized responses, and the continued need for manual follow-up by technicians or Telkomsel Grapari partners. This research aims to assess the effectiveness of OCA using William N. Dunn’s six indicators of policy evaluation: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A qualitative descriptive approach was applied, with data collected through observation, interviews with customers, Telkom staff, the Plasa Witel manager, and Grapari technicians, as well as document analysis. Informants were selected using purposive sampling, while data validity was tested through source triangulation and analyzed using Miles, Huberman, and Saldana’s (2014) model. The findings reveal that the OCA chatbot contributes positively to digital service transformation by improving cost efficiency, providing equal access, and filtering customer data before escalation. Nevertheless, its effectiveness is limited, as most technical complaints still require human intervention. The novelty of this study lies in its comprehensive evaluation of chatbot services in the context of public digital service transformation, highlighting the importance of integrating automated systems with human support. Continuous improvements in accuracy, consistency of standard operating procedures, and stronger integration with technical teams are necessary to optimize OCA’s role as a reliable, efficient, and inclusive complaint-handling service.